Effect of lower body compression garment in running mechanics - Borras, X.; Balius, X.; Drobnic, F. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of the research was to determine if compression shorts affected running mechanics. Eight active male participated in the study ([mean x SD] age 25.6 x 10.3 years; height 177.9 x 2.9 cm; weight 71.9 x 7.4 kg). Three conditions were evaluated, compression shorts, standard Lycra shorts and underwear. Movement mechanics was evaluated using 2D videography of a progressive running test with initial velocity of 10 km/h and increments of 1km/h every minute. The increase of velocity affect knee and hip maximum and minimum extension angles which is translated to an increase of stride length. Compression reduced hip and knee flexion angle during recovery. Nevertheless, changes in movement mechanics did not interfere with length or frequency of stride indicators of running efficiency.